Exploring the Meaning of a Field Trip: Recreational Activity or Learning Activity? - Amri, Saiful; Rahmadonna, Sisca (FKIP Universitas Lampung, 2025)
Abstract: Exploring the Meaning of a Field Trip: Recreational Activity or Learning Activity?. Objective: The main objective of the research is to identify and understand the psychological meanings embedded in the field trip experience and how students interpret this activity in both educational and recreational contexts. Methods: This study employs a qualitative phenomenological analysis method to explore students' perceptions of field trips as a learning activity in a Senior High School in Yogyakarta City. Findings: Out of 24 respondents, only 4 students perceived the field trip as a formal learning activity. Fifty percent of respondents viewed it as a combination of learning and recreation, while the remaining third interpreted it solely as a recreational activity. The findings reveal that students' perceptions of field trips are influenced by personal experiences, the organization of the trip, and its integration into the curriculum. This research underscores the importance of carefully designing field trips to achieve educational goals while providing a recreational element. Conclusion: As such, the multifaceted interpretation of field trips can be utilized by educators to create holistic and enjoyable learning experiences that not only meet curriculum objectives but also enhance student engagement and motivation.Keywords: fieldtrip, field visit, education, recreation.